Effect of supplementation of maize stover with foliage of various tropical multipurpose trees and Lablab purpureus on intake, rumen fermentation, digesta kinetics and microbial protein supply of sheep - Hindrichsen, I.K.; Osuji, P.O.; Odenyo, A.A.; Madsen, J.; Hvelplund, T. (Elsevier, 2004)
Foliage of four multipurpose trees (Calliandra calothyrsus, Chamaecytisus palmensis, Leucaena diversifolia and Vernonia amygdalina) and a woody leguminous perennial (Lablab purpureus) were evaluated for their potential as protein supplements for sheep fed maize stover ad libitum. The chemical composition of the feed was analysed, and maize stover degradation, rumen kinetics, passage rate were measured and enumeration of microbial population in the rumen was done. L. diversifolia had the highest content of nitrogen (33.4g/kg dry matter (DM)) while L. purpureus had the lowest one with 31.0g/kg DM. V. amygdalina and C. calothyrsus had a low palatability and were eaten at levels largely varying among sheep and days; these two supplements were excluded from further analysis. The apparent digestibility of nitrogen for the diets supplemented with L. diversifolia was 0.338 and expressed a tendency (P=0.06) to be lower compared to 0.583 and 0.546 found with the C. palmensis and the L. purpureus diet, respectively. The apparent neutral detergent fibre-bound nitrogen (NDF-N) digestibility of L. diversifolia was negative (-1.19) and lower (PL. diversifolia was also found to have a lower (PC. palmensis. With L. diversifolia, the urinary N loss was lowest (PC. palmensis and L. purpureus, respectively. There was no significant difference between the three supplements on the potential or effective degradability of maize stover in the rumen (assuming a constant rumen outflow rate), neither was there any difference among supplements in the counts of total bacteria or protozoa in rumen fluid. The study suggests that the nutritive value of the five supplements investigated can be ranked as L. purpureus, C. palmensis, L. diversifolia, C. calothyrsus and V. amygdalina.